2017
DOI: 10.1007/s00203-016-1331-4
|View full text |Cite
|
Sign up to set email alerts
|

Stress response physiology of thermophiles

Abstract: Thermo (or hyperthermo) philic microorganisms are ubiquitous having a wide range of habitats from freshly fallen snow to pasteurized milk to geothermal areas like hot springs. The variations in physicochemical conditions, viz., temperature, pH, nutrient availability and light intensity in the habitats always pose stress conditions for the inhabitants leading to slow growth or cell death. The industrial processes used for harvesting secondary metabolites such as enzymes, toxins and organic acids also create str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 263 publications
0
22
0
Order By: Relevance
“…The term "thermophiles" is devoted to microorganisms revealing optimal growth temperature above 45 • C [1]. Actually, these microbes are ubiquitous since they can be isolated from a wide range of habitats from freshly fallen snow to pasteurized milk to geothermal areas like hot springs [2]. Currently, thermophiles attract attention of industrial biotechnologists since bioprocesses operated at elevated temperatures have a number of advantages, including a reduced risk of microbial contamination, lowered jeopardy by phage infection, improved solubility of substrates such as polysaccharide-rich resources, continuous and direct recovery of volatile metabolites from fermentation broth such as alcohols or volatile fatty acids (VFAs) and decreased cooling costs and demands for cooling water due to the higher temperature difference between bioreactor and the ambient air.…”
Section: Introductionmentioning
confidence: 99%
“…The term "thermophiles" is devoted to microorganisms revealing optimal growth temperature above 45 • C [1]. Actually, these microbes are ubiquitous since they can be isolated from a wide range of habitats from freshly fallen snow to pasteurized milk to geothermal areas like hot springs [2]. Currently, thermophiles attract attention of industrial biotechnologists since bioprocesses operated at elevated temperatures have a number of advantages, including a reduced risk of microbial contamination, lowered jeopardy by phage infection, improved solubility of substrates such as polysaccharide-rich resources, continuous and direct recovery of volatile metabolites from fermentation broth such as alcohols or volatile fatty acids (VFAs) and decreased cooling costs and demands for cooling water due to the higher temperature difference between bioreactor and the ambient air.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, when micro‐organisms are heat‐stressed they evoke a variety of physiological responses, including the production of DNA‐binding proteins, upregulation of the reactive oxygen species (ROS) detoxification system, solute accumulation, and the expression of heat shock proteins (Hsps), to name a few . Since mitochondria appear to be operating at an elevated temperature, relative to the cytosol, the question of whether similar protective mechanisms are operating within mitochondria arises.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, when micro-organisms are heat-stressed they evoke a variety of physiological responses, including the production of DNA-binding proteins, upregulation of the reactive oxygen species (ROS) detoxification system, solute accumulation, and the expression of heat shock proteins (Hsps), to name a few. [4] Since mitochondria appear to be operating at an elevated temperature, relative to the cytosol, the question of whether similar protective mechanisms are operating within mitochondria arises. Interestingly, bulk differential scanning calorimetry studies on cellular organelles, including the cytosol and mitochondria, revealed melting temperatures (T m values) of ≈40°C, suggesting that, on average, thermolabile proteins appear to be present in all cellular organelles and compartments.…”
Section: Introductionmentioning
confidence: 99%
“…Sometimes the same microorganism owns more metal resistance mechanisms; for example, Escherichia coli possesses either a copper active transport system (CopA) and another system based on multicopper oxidases (CueO) and CusCFBA transport system for periplasmic copper detoxification [ 23 , 44 ]. These resistance mechanisms are often activated as stress response [ 45 , 46 ]; understanding their underpinning molecular basis is crucial for application in the environmental monitoring of metal contamination (biosensing) and/or to set up bioremediation processes [ 14 , 47 , 48 ].…”
Section: Heavy Metalsmentioning
confidence: 99%